Editorial - Katherine Bullock (International Institute of Islamic Thought, 2008)
This year AJISS turns twenty-five. In 1983, during a meeting of the Association of Muslim Social Scientists’ (AMSS) executive board in Plainfield, Indiana, the pros and cons of establishing a journal were discussed in great detail and at length. The board members, Dr.Waheed Fakri (president), Dr. Sulayman S. Nyang (vice president), and Dawood Zwink (treasurer) agreed that the United States needed a Muslim-led and Muslim-organized scholarly publication to address important issues at home and abroad. In their vision, the journal would educate university and college students, as well as policymakers, with respect to the life and conditions ofMuslims in the social sciences. In addition, the journal would be a vehicle for articulating and aggregating Muslim views and understanding of the social sciences. Another objective was to provide a forum for Muslim scholars, and especially for those associated with the AMSS, to publish their research. At the time, it was felt that Muslim scholars engaged in social science research projects with an Islamic perspective found mainstream scholarly journals inhospitable. The board thought that the proposed journal would become – as it has – a forum for cutting-edge research in the social sciences and the humanities, employing both the standard social science research methodologies as well as the Islamic theoretical and methodological perspectives. Two issues were critical: (1) obtaining the financial resources needed to sustain the proposed journal and (2) its viability and effectiveness. After the go-ahead decision had been taken, and in order to establish the journal, the board members drew upon the intellect and services of AMSS members as well as friends and sympathizers. With this in mind, Dr. Mumtaz Ahmad, a respected and activeAMSS member and friend of Dr. Nyang, was proposed as the journal’s co-editor. Dr. Nyang became the editor-in-chief and Dr. Ahmad, a former editor of a scholarly journal in Pakistan, became the editor. Several prominent Muslims were invited to serve on the advisory board to widen the circle of involvement ...